Revolutionizing sugar beet yield and quality in saline sandy soil through synergistic humic acid, glauconite, and boron foliar application - Mohamed A. Abd El-Aziz; Nevien Elhawat; Ahmed K. H. Amer; Asmaa F. M. Badawy; Amira E. El-Sherief; R. M. Khalifa; Mahmoud M. A. Shabana; Tarek Alshaal (Plant and Soil, 2026)
Aims Saline sandy soils severely constrain sugar beet ( Beta vulgaris L.) productivity due to low nutrient retention, high salinity, and micronutrient imbalances, particularly boron deficiency. Although humic substances, glauconite, and boron fertilization have individually or pairwise improved crop performance, no previous field study has evaluated their ternary, dose-optimized integration as a multifunctional soil–plant management strategy under saline sandy conditions. Methods This study investigated, for the first time, the combined application of soil-applied humic acid (600 kg/ha), glauconite (1100 kg/ha), and graded foliar boric acid (0, 1900, and 3800 g/ha) to test the hypothesis that their complementary physicochemical and physiological mechanisms would generate synergistic improvements in soil quality, crop performance, and sugar productivity beyond additive effects. Field experiments were conducted over two consecutive growing seasons (2021–2022) in West Minya, Egypt, using a split-plot design. Results The integrated high-dose treatment (HG3800) significantly enhanced leaf area index (by 75%), chlorophyll content (46–71%), and net photosynthetic rate (40–128%) relative to the control. Root yield increased by 27% (reaching 56.7 ton/ha), while sugar yield rose by up to 79% (11.5 ton/ha). Sucrose concentration reached 20.4%, with reduced impurity indices and improved extractable sugar percentage (up to 90%). Based on fermentable sugar yield, the HG3800 treatment corresponded to a substantial increase in theoretical bioethanol output potential per hectare. Concurrently, soil electrical conductivity declined by 24%, soil organic matter increased, and bulk density decreased, reflecting improved soil structure and salinity mitigation. Conclusions The ternary, dose-optimized integration of humic acid, glauconite, and foliar boron represents a novel agronomic strategy that simultaneously enhances soil physicochemical properties, physiological efficiency, and fermentable sugar production. By directly linking yield gains to increased bioethanol feedstock potential, this approach offers a scalable and multifunctional pathway for sustainable bioenergy-oriented sugar beet production in salt-affected sandy soils.